АНАЛІЗ ТА ІНТЕРПРЕТАЦІЯ РЕЗУЛЬТАТІВ ДОСЛІДЖЕННЯ (Педагогіка вищої та середньої школи, 2008)
Forming experiment of this probe has proves usage the personal rough approach for creation of indispensable qualities for the future managers o f entrepreneurial business.